The response of the modern legal systems to domestic violence: Comparative analysis of some of the European countries and New York State, USA - Milivojević Sanja K. (Temida, 2003)
In the last few years of XX century domestic violence was in focus of interest in majority of European countries and worldwide. The severity of consequences that this type of violence generates to victims and other members of their families (indirect victims), the development of women's rights movement, large number of research and scholars papers that warn about danger from this violence, led to the criminal prosecution of domes tic violence and establishment of large scale of measures for victims protection, prevention of further victimization, punishment of perpetrators and minimization of negative consequences of violence. The aim of this paper is to compare modern European legislations as well as the legislation of New York State, USA, in order to consider possible further development in fighting this complex social problem in our society and practice.